INFECTIOUS MYONECROSIS VIRUS (IMNV) IN PACIFIC WHITE SHRIMP, Litopenaeus vannamei IN INDONESIA - Taukhid Taukhid; Yani Lestari Nur’aini (Indonesian Aquaculture Journal, 2008)
The aquaculture industry in Indonesia has been growing rapidly and plays an important role in rural development and export earning. Penaeid shrimp culture in Indonesia has become a leading export earning in fisheries sector. The main constraint encountered with shrimp culture has always been associated with disease outbreaks, especially, caused by viral agents. The Pacific white shrimp (Litopenaeus vannamei) was unofficially introduced to Indonesia in 1999, and officially approved by Indonesian government in 2001. By the end of 2007, the Pacific white shrimp has been cultured in more than 17 provinces. The Taura Syndrome (TS) disease was detected in Indonesia in 2002, and the disease is currently found in at least 10 provinces. The Infectious Myonecrosis (IMN) is an emerging disease for L. vannamei in Indonesia, first detected in May-June 2006, causing significant mortalities in grow-out ponds. The IMN is characterized by an acute onset of gross signs: focal to extensive whitish necrotic areas in the striated muscle, especially on the distal abdominal segments and tail fan. White necrotic areas become reddened similar to the color of cooked shrimp. The outbreak resulted in elevated mortalities was initially associated with a chronic course of persistent low level mortalities. Up to date, IMN was detected in East Java, Bali, and West Nusa Tenggara provinces. This paper is a brief review of the epidemiological study of IMN disease of Pacific white shrimp in Indonesia: the status of outbreaks, surveillance, and disease diagnosis, and control measures.